FAR DISTANCE LEARNING SYSTEM FOR WEB-BASED IN ENGLISH COURSES USING PHP AND MYSQL - HARIS MUNANDAR (Jurnal Sistem Informasi, 2009)
Seeing the concept of traditional learning carried out today, the students and teachers met at a certain place and time. Traditional learning systems will be replaced with a distance learning system is more practical and is not affected space and time, thus providing benefits to various groups of owners of the courses do not have to build infrastructure to the benefit of the public felt had the opportunity to learn more, which available on the website with topics including reading, writing, conversation. In the distance learning is the main focus of students. Students to be independent and responsible for learning. Distance learning atmosphere will force the students to play a more active role in learning. Adapt to the English language since primary school age is one of the best ways for children to be fluent in English in the future.  Results from a distance learning system on  web-based English course with a programming language php and mysql for database programming, website shown in the form in which there are buttons that allows students to learn without being accompanied by instructors. These buttons are home, category, curriculum, teacher. Distance learning provides an alternative educational equity and provide solutions to problems found in the  concept of traditional  education is one of geographical location.